Bacillus spore-forming probiotics: benefits with concerns?. (4th July 2022) - Todorov, Svetoslav Dimitrov; Ivanova, Iskra Vitanova; Popov, Igor; Weeks, Richard; Chikindas, Michael Leonidas
Abstract: Representatives of the genus Bacillus are multifunctional microorganisms with a broad range of applications in both traditional fermentation and modern biotechnological processes. Bacillus spp. has several beneficial properties. They serve as starter cultures for various traditional fermented foods and are important biotechnological producers of enzymes, antibiotics, and bioactive peptides. They are also used as probiotics for humans, in veterinary medicine, and as feed additives for animals of agricultural importance. The beneficial effects of bacilli are well-reported and broadly acknowledged. However, with a better understanding of their positive role, many questions have been raised regarding their safety and the relevance of spore formation in the practical application of this group of microorganisms. What is the role of Bacillus spp. in the human microbial consortium? When and why did they start colonizing the gastrointestinal tract (GIT) of humans and other animals? Can spore-forming probiotics be considered as truly beneficial organisms, or should they still be approached with caution and regarded as "benefits with concerns"? In this review, we not only hope to answer the above questions but to expand the scope of the conversation surrounding bacilli probiotics.